Bilateral hypoplasia of the internal carotid artery - Dhananjaya I Bhat (Indian Journal of Radiology and Imaging, 2011)
Agenesis and hypoplasia of the internal carotid artery (ICA) are rare congenital anomalies, occurring in less than 0.01% of the population. We report a rare case of bilateral hypoplasia of the ICA in a patient with post-traumatic subarachnoid hemorrhage. We describe the embryological development of the cerebral vasculature and present a review of literature.